RE-DESIGN PINTU GRAVING DOCK KAPASITAS 6000 DWT - Stefanus Parmada (2022)
The Graving Dock door is a dock door that is directly connected to the sea, where this door must suppress a lot of pressure from the sea to keep the dock dry. The graving dock door must be kept tightly closed to keep the dock dry at all times. This study aims to explain the modification process and analyze the effects that will occur on the dock after the modification of this dock door. The method used in this study is a reference method based on BKI Rules For Hull Vol. II 2021. The result of this research is to produce a new 6000 DWT graving dock door with a less frequent variation of the ivory distance, where the graving dock door generally uses an ivory spacing variation of 400-500 mm, but in this design it has a variation of 600 mm with a size The main dock door is 21.7 m long, 2.2 m wide and 7.5 m high. The door with this variation has a maximum stress of 108.58 N/mm2, where this maximum stress is a measurement of the strength of a static material where the graving dock is not like a ship which is a moving (dynamic) material/building. In this graving dock door, concrete is carried out at the bottom of the graving dock door to reduce the buoyancy point due to increase the stability of this graving dock door which will withstand hydrostatic pressure from the sea as in Bernoulli's law.